Antigua and the Antiguans: a full account of the colony and its inhabitants from the time of the Caribs to the present day, interspersed with anecdotes and legends : also, an impartial view of slavery and the free labour systems, the statistics of the island, and biographical notices of the principal families, Volume 2TT - (Saunders and Otley, 1844)
Découverte en 1493 par Christophe Colomb, l'île d'Antigua située dans les Petites Antilles sera baptisée ainsi en l'honneur de l'église de Santa Maria la Antigua de Séville. Elle sera plus tard, en 1632, colonisée par les Britanniques.